KECERDASAN EMOSIONAL, HAMBATAN PERUBAHAN, DAN BUDAYA ETNIK, PENGARUHNYA TERHADAP KINERJA MELALUI MANAJEMEN PERUBAHAN - Agus Fauzi (Pasca Sarjana Universitas Satya Negara Indonesia, 2018)
The study aims to produce a model of research that relates to the variable of emotional quality, resistance to change, etnic culture, change management, dan performnce. This article also aims to produce a model of a study to evaluate the influence of emotional quality, resistance to change, and etnic culture, on performnce either directly or through change management, both partially and simultaneously. This article is a review of the literature, so that method being used is a literature review. This study is conducted by grinding theories that have been established. The study also sourced and based on the results of previous research, especially empirical research results that related to the variables that were being studied. In addition, if it is continued in empirical research, the study population will include Abdi Sipil Negara (ASN) of Region Government. This study produces a proposed model for further study that explains the relationship between emotional quality, resistance to change, etnic culture, change management and performnce of Abdi Sipil Negara (ASN) of Region Government in Jakarta.